The Code-Switching Used in Deddy Corbuzier’s Youtube Podcast - I Putu Suardhana (Journal Social and Humaniora, 2022)
This undergraduate thesis is entitled “Code-Switching in Deddy Corbuzier’s Youtube Podcast”. This study is focusing to find out the types of Code-Switching and find out of the function of Code-Switching during the speech of Deddy Corbuzier and Azka Corbuzier on the podcast on Youtube. The data of this study were taken from the Youtube channel. The data were focused on speech while talking using mixed language between Indonesian language and English language. The data was collected through documentation and library research with note-taking techniques. The method that is used to analyze the data is the descriptive-qualitative method. The theories used for this study are the theory proposed by Poplack (1980) about three types of code-switching, there are tag switching, inter-sentential switching, and intra-sentential switching, and theory proposed by Hoffman (1991) about seven reasons of code-switching, there are talking about a particular topic, quoting somebody else, being emphatic about something, interjection (inserting sentence fillers or sentence connectors), repetition used for clarification, the intention of clarifying the speech content for the interlocutor, and expressing group identity.